2021
DOI: 10.1002/ecs2.3789
|View full text |Cite
|
Sign up to set email alerts
|

Of olives and carp: interactive effects of an aquatic and a terrestrial invader on a stream‐riparian ecosystem

Abstract: Multiple invasive species may interact, influencing one another and generating synergistic effects on food webs and ecosystem processes. We investigated the interaction between two non‐native species widespread in the western USA: common carp (Cyprinus carpio) and Russian olive (Elaeagnus angustifolia), an invasive riparian tree associated with di‐nitrogen fixation. Deep Creek, Idaho, was an International Biological Program site in the early 1970s; at that time, carp were rare and Russian olive was absent. Sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 93 publications
0
5
0
Order By: Relevance
“…the subterminal mouths of suckers are inefficient for surface feeding) because they did not evolve with fruiting riparian trees. Olive availability may provide a disproportionate advantage to nonnative catfish and carp, which have evolutionary histories of frugivory (Chick et al, 2003; Heinrich et al, 2021). However, the net effects of olive subsidies likely depend on consumer traits in the recipient community.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…the subterminal mouths of suckers are inefficient for surface feeding) because they did not evolve with fruiting riparian trees. Olive availability may provide a disproportionate advantage to nonnative catfish and carp, which have evolutionary histories of frugivory (Chick et al, 2003; Heinrich et al, 2021). However, the net effects of olive subsidies likely depend on consumer traits in the recipient community.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, Heinrich et al (2021) found that ~58% of common carp tissues were derived from olive fruit in a small Idaho stream. Using bioenergetic modelling, Heinrich et al (2021) also reported that olive fruit provided a trophic subsidy that facilitated the invasion of nonnative common carp and that the subsidy resulted in higher carp biomass after the invasion. A similar relationship may exist between olive and catfish, but catfish are less adapted for consuming seeds (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Invasive species can significantly alter riverine food webs by rerouting basal resources that support consumers (Moore et al, 2012), altering nutrient cycling (Atkinson et al, 2010; Capps & Flecker, 2013; Heinrich et al, 2021), and competing with and preying upon native organisms (Baxter et al, 2004; Koel et al, 2019). Understanding the impacts of invasive species—and if/how they can be controlled—often necessitates a food web approach.…”
Section: Critical Management Questionsmentioning
confidence: 99%